Ocular bobbing with survival. Issue 1 (January 1976) - Clarke, Charles; Stern, Richard
Abstract : A case is described of prolonged ocular bobbing with survival after subarachnoid haemorrhage from a pontine arteriovenous malformation. Hitherto, this sign has usually been associated with a rapidly fatal outcome.